Translating Finnish Pedagogical Excellence into Sustainable School Management: Strategies for Fostering Equity and Diversity in Primary Education - Muchammad Tholchah; Devi Prasad Bhattarai (PT. Berkah Smart Academica, 2026)
This study aims to analyze strategies for translating Finnish pedagogical excellence into sustainable primary school management, focusing on fostering equity and diversity. This evaluation urgently required as many traditional school management models as possible in centralized systems to struggle to balance rigorous academic standards with student well-being and inclusive practices. The novelty of this research lies in the development of a